2003
DOI: 10.1111/j.1939-1676.2003.tb02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I in Pastured and Race-Training Thoroughbred Horses

Abstract: Cardiac troponin I (cTnI), a myocardial polypeptide, is a highly sensitive and specific biomarker of myocardial injury in people and dogs. The structure of cTnI is highly conserved across species, and equine myocardium has high reactivity with human immunoassays. The purpose of this study was to describe cTnI concentrations in normal pastured and race-training Thoroughbred horses. Ten horses on pasture and 10 horses in race training were studied. Horses were considered normal on the basis of physical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 13 publications
5
49
0
5
Order By: Relevance
“…The range of serum cTnI concentrations observed in the present study is similar to the ranges reported using the same immunoassay in normal pasture and race-training thoroughbred horses [12,19]. In order to quantify the intensity of effort carried out by horses during physical activity, it becomes necessary to determine the genesis of the physiological response that depends on the kind, speed, distance, and duration of gait.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The range of serum cTnI concentrations observed in the present study is similar to the ranges reported using the same immunoassay in normal pasture and race-training thoroughbred horses [12,19]. In order to quantify the intensity of effort carried out by horses during physical activity, it becomes necessary to determine the genesis of the physiological response that depends on the kind, speed, distance, and duration of gait.…”
Section: Discussionsupporting
confidence: 81%
“…Although all the horses included had normal physical examinations, ECG, and echocardiograms, early myocardial disease might not have been detectable by these tests. Similar considerations were made by in horses in pastured and race training thoroughbred horses Phillips, et al [19]. Histopathology of the heart tissues would have been the gold standard for detection of myocardial cell injury, but it was not possible in the present study [19].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…25 Evaluation of cTnI in the horse is limited, except for reports that documented cTnI values in horses in training or at rest and for isolated case reports of acute ventricular tachycardia. 3,9,13,19,27,30 Recently, the present authors reported that cTnI, measured by either the access immunoassay a or the point-of-care analyzer i- STAT 1, b is an accurate method of detecting cardiac disease in the horse (MS Kraus, SA Jesty, AR Gelzer, et al: 2007, Characterization of cardiac troponin I as an indicator of cardiac damage in horses utilizing an i-STAT-1. Abstract in proceedings of the Annual American College of Veterinary Internal Medicine Forum.…”
Section: Introductionmentioning
confidence: 96%
“…404 ng/ml aufwiesen. In einer anderen Studie (Phillips et al 2003) wird der Normwert für equines cTnI mit < 0,15 ng/ml angegeben. Mehrere Studien zeigten bereits, dass der humane cTnI Immunoassay auch beim Pferd angewendet werden kann, da die Herzgewebereaktivität, gemessen mit einem humanen Immunoassay, beim Hund und Pferd sehr ähnlich sind (O`Brian et al 1997).…”
Section: Introductionunclassified